2002
DOI: 10.1002/oa.623
|View full text |Cite
|
Sign up to set email alerts
|

Spondylolysis in Inuit skeletons from Arctic Canada

Abstract: Inuit skeletons from archaeological sites in Arctic Canada were examined for the presence of spondylolysis. The largest series represent the Thule culture and historic Inuit from northwest Hudson Bay and Labrador, and Sadlermiut from Southampton Island. The condition was found in 90 individuals, with a total of 120 affected vertebrae producing 198 hemi-arch defect sites.As in other studies, L5 is affected most frequently, followed by L4 and L3, but examples of L1, L2, L6, and S1 involvement are represented. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
1
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 32 publications
3
23
1
2
Order By: Relevance
“…Burials here span the 10th-19th centuries AD, but are predominantly from 11th to 14th centuries (Bayliss et al, 2007). This is not the highest known population frequency, as Inuit populations are reported to have a prevalence of 40% or higher (reviews in Merbs, 2002;Fibiger and Knü sel, 2005). Still, it highlights differences among populations in the prevalence of these defects.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…Burials here span the 10th-19th centuries AD, but are predominantly from 11th to 14th centuries (Bayliss et al, 2007). This is not the highest known population frequency, as Inuit populations are reported to have a prevalence of 40% or higher (reviews in Merbs, 2002;Fibiger and Knü sel, 2005). Still, it highlights differences among populations in the prevalence of these defects.…”
mentioning
confidence: 59%
“…Higher activity levels have been suggested as a potentially influential factor (review in Mays, 2006b), as defects are often more frequent in archaeological than in modern populations (Merbs, 1983;Bridges, 1989;Arriaza, 1997;Merbs, 2002;Fibiger and Knü sel, 2005). Certainly, the occurrence of spondylolysis is influenced by mechanical variables (Nathan, 1959;Wiltse, 1962;Newman, 1963;Wiltse et al, 1975;Cyron et al, 1976;Farfan et al, 1976;Cyron and Hutton, 1978;Cyron et al, 1979;Troup, 1979;Dietrich and Kurowski, 1985).…”
Section: Introductionmentioning
confidence: 94%
“…Following Merbs (2002), the author noted the presence or absence of the condition, when it occurred, whether the separation was partial or complete, which vertebrae were affected, whether the condition was unilateral (along with the side it occurred on) or bilateral, and whether there was evidence of healing.…”
Section: Samplementioning
confidence: 99%
“…Another interesting twist is that as individuals grow very old, spondylolysis seems to decrease. Merbs (2002) noted that the decrease in spondylolysis rates in older adults could relate to the healing of fractures, and thus prior spondylolysis escapes detection. However, this must be coupled with older individuals ceasing their strenuous activities, since Reiter et al (2006) and Bridges (1989) have both found spondylolysis in elderly individuals.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation